2008
DOI: 10.1136/tc.2008.025809
|View full text |Cite
|
Sign up to set email alerts
|

Reading culture from tobacco advertisements in Indonesia

Abstract: Background: Tobacco advertising in Indonesia is among the most aggressive and innovative in the world, and tobacco advertisements saturate the environment. Tobacco companies are politically and financially powerful in the country because they are one of the largest sources of government revenue. As a result, there are few restrictions on tobacco marketing and advertising. National surveys reveal that 62% of men and 1% to 3% of women are smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(115 citation statements)
references
References 27 publications
(26 reference statements)
1
109
0
5
Order By: Relevance
“…the Marlboro Man and sponsorship of motor racing, alongside those of male romantic and financial success (13). Nichter et al (14) reviewed over five years of advertising of kretek cigarettes, a clove-infused local variety that holds 90% of market share in Indonesia, where male smoking prevalence is 62% (vs 1-3% among women). The main themes identified included 'smoking to enhance masculinity, and smoking as a means to uphold traditional values while simultaneously emphasizing modernity and globalization'.…”
Section: Gender Culture and Tobaccomentioning
confidence: 99%
“…the Marlboro Man and sponsorship of motor racing, alongside those of male romantic and financial success (13). Nichter et al (14) reviewed over five years of advertising of kretek cigarettes, a clove-infused local variety that holds 90% of market share in Indonesia, where male smoking prevalence is 62% (vs 1-3% among women). The main themes identified included 'smoking to enhance masculinity, and smoking as a means to uphold traditional values while simultaneously emphasizing modernity and globalization'.…”
Section: Gender Culture and Tobaccomentioning
confidence: 99%
“…Moreover, through their sponsorships and philanthropic activities, the tobacco companies have managed to convince the adolescents, that through smoking, however, they have provided positive contributions to society. The Indonesian adolescents have become the main target of cigarette marketing by tobacco companies, as the cigarette marketing are always associated with adolescents, including cigarette advertising featured by young celebrities, cigarette packs designed attractive, and favorite events among the adolescents sponsored by the tobacco companies (S. Lee et al, 2012;Nichter et al, 2009). Empirical research has confirmed that approximately 90% of Indonesian adolescents have been exposed by the tobacco advertising and promotion (GYTS, 2009).…”
Section: Anti-smoking Campaignsmentioning
confidence: 92%
“…Some studies have confirmed that to increase their sale, Indonesian tobacco companies aggressively used small retailer outlets to advertise and to market tobacco products, especially to adolescents (Mardian, 2011;Nichter et al, 2009). …”
Section: Enforcing Ban On Cigarette Marketing Toward Teenagersmentioning
confidence: 99%
“…Most Indonesian smokers smoke kreteks, hand-rolled or machine-rolled clove-flavoured cigarettes, which account for over 92% of retail sales volume3 and, like all tobacco products, cause serious diseases and death 2. Smoking is the cultural norm in Indonesia and plays a central role in social and political systems 4. In December 2009, Indonesian governmental officials announced intentions to consider ratification of WHO Framework Convention on Tobacco Control (FCTC) 5.…”
Section: Introductionmentioning
confidence: 99%